(untitled) (American Journal of Pedagogical and Educational Research, 2022)
In this work the problem of leadership as the main mechanism of regulation of an enterprise is raised on the example of Russian organizations. Also outlines the main concepts related to leadership and presents data and results of the survey on the qualities of a leader. Special attention is given to the identification and description of the main strategies of leadership in Russia. Situational approaches and theories of leadership in general are also highlighted.